2012
DOI: 10.1287/opre.1110.1011
|View full text |Cite
|
Sign up to set email alerts
|

Price of Correlations in Stochastic Optimization

Abstract: When decisions are made in the presence of large-scale stochastic data, it is common to pay more attention to the easy-to-see statistics (e.g., mean) instead of the underlying correlations. One reason is that it is often much easier to solve a stochastic optimization problem by assuming independence across the random data. In this paper, we study the possible loss incurred by ignoring these correlations through a distributionally-robust stochastic programming model, and propose a new concept called Price of Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(129 citation statements)
references
References 55 publications
2
119
0
Order By: Relevance
“…Their results show that our Theorems 3 and 4 will also hold in an adaptive submodular setting. In addition, see Agrawal et al (2012) who introduce the notion of price of correlations and study the effect of ignoring correlations in optimization problems.…”
Section: Large Adaptivity Gap Without the Independence Assumptionmentioning
confidence: 99%
“…Their results show that our Theorems 3 and 4 will also hold in an adaptive submodular setting. In addition, see Agrawal et al (2012) who introduce the notion of price of correlations and study the effect of ignoring correlations in optimization problems.…”
Section: Large Adaptivity Gap Without the Independence Assumptionmentioning
confidence: 99%
“…For a monotone submodular function f , [14] showed that the expected value of f over any distribution of subsets is at most a constant factor larger than the expectation over subsets drawn from the product distribution with the same marginals. This bound on the correlation gap has been very useful in the past decade with applications in optimization [17], mechanism design [1,51,11,8], influence in social networks [46,7], and recommendation systems [40].…”
Section: Theorem 13 (Monotone Subadditivementioning
confidence: 99%
“…We recall some notation for to extend submodular functions from the discrete hypercube {0, 1} n to relaxations whose domain is the continuous hypercube [0,1] n . For any vector x ∈ [0, 1] n , let S ∼ x denote a random set S that contains each element i ∈ [n] independently w.p.…”
Section: Submodular and Matroid Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…(In the first-price auction an agent with value v wins with probability v and pays her bid which is v/2; in the secondprice auction an agent with value v wins with probability v and pays the expected value of the other agent conditioned on being at most v which is v/2.) Both the first-and second-price auction with bidder values drawn uniformly from [0,1] are examples of independent, single-dimensional, and linear utilities. In these auction problems, the auctioneer also has a feasibility constraint that at most one agent can win the item, i.e., i x i ≤ 1.…”
Section: Independent Single-dimensional and Linear Utilitiesmentioning
confidence: 99%